Le cadre juridique de la libre circulation des biens et des services dans la Communauté économique de l’ASEAN - Chhak, Limcheang (Université Côte d'Azur, 2020)
La recherche a essayé d’affiner les phénomènes juridiques de la libéralisation des biens et des services, dite de première génération, en faveur d’une politique d’intégration économique régionale, sous l’emprise de la mondialisation, afin d’établir la Communauté économique de l’ASEAN. Cependant, la question de l’existence des règles substantielles de droit est sous-estimée au regard des juristes internationaux, et est pertinente pour l’Association ; autrement dit, l’ASEAN se fonde principalement sur le soft-law, ASEAN Way, qui a ralenti effectivement la réalisation de sa politique d’intégration économique. Afin de surmonter de ces défis, cette thèse a opté une approche de droit international public afin d’examiner le mécanisme d’élaboration des règles conventionnelles ainsi que non conventionnelles de cet Association. De plus, le droit international économique est également un choix méthodologique pour ce travail de recherche sur les questions techniques essentielles dans le processus de la création du marché unique de l’ASEAN. En résultat, nous avons découvert que le droit matériel de l’ASEAN est bien existé et continue à développer progressivement au sens propre du droit international. D’ailleurs, les mécanismes institutionnels administratifs ainsi que juridictionnels sont été observés dont leur fonctionnement est impliqué de manière pragmatique pour la mise en œuvre de ces règles matérielles en matière de la libre circulation des biens et services. Malgré que ces règles de droit connaissent les critiques tant à ses effectivité et efficacité à cause de sa caractère souple et non contraignant, l’harmonisation juridique sectorielle est achevée vers la direction de la construction du droit communautaire de l’ASEAN. En conclusion, la régionalisation économique de l’ASEAN se fonde effectivement sur son cadre juridique propre, en basant sur le pluralisme juridique et est conforme au droit international. Research has tried to refine the legal phenomena of the liberalization of goods and services, known as first generation, in favor of a regional economic integration policy under the influence of globalization, in order to establish the ASEAN Economic Community. However, the question of the existence of substantive rules of law is underestimated in the eyes of international lawyers and it is relevant. In other words, ASEAN is mainly based on soft law, namely ASEAN Way, which has effectively slowed down the implementation of its economic integration policy. In order to overcome these challenges, this thesis opted for an approach of public international law in order to examine the mechanism of formation of conventional as well as non-conventional rules of this in ASEAN. In addition, international economic law is also a methodological choice for this research work on essential technical questions in the process of creating the ASEAN Single Market. As a result, we have discovered that ASEAN substantive law does exist and continues to develop gradually in the proper sense of international law. Moreover, the administrative as well as jurisdictional institutional mechanisms have been observed, their operation of which is implicated in a pragmatic manner for the implementation of these material rules regarding the free movement of goods and services. Despite the fact that these rules of law are criticized both for their effectiveness and efficiency because of their flexible and non-binding nature, sectoral legal harmonization is complete towards the direction of the construction of ASEAN Community Law. In conclusion, the economic regionalization of ASEAN is effectively established on its own legal framework, based on legal pluralism and is consistent with international law.
Publication Title: theses.fr

Desafios da cooperação intra-regional e perspectivas da integração tripartida entre SADC-EAC-COMESA : avaliação das implicações para SADC - Banze, Vasco Alberto (Universidade Federal do Rio Grande do Sul, 2020)
A Integração Tripartida entre Comunidade de Desenvolvimento da África Austral (SADC), Comunidade da África Oriental (EAC) e Mercado Comum de África Oriental e Austral (COMESA) é uma inciativa de Chefes de Estado e de Governos das três Comunidades Económicas Regionais (CERs) em integrar seus separados programas numa única área de livre comércio. A iniciativa enquadra-se no contexto do Plano de Acção de Lagos (1980) e do Tratado de Abuja (1991) que consideram as CERs como pilares para criação da Comunidade Económica Africana (CEA). A Tese tem como principal objectivo analisar os desafios da cooperação intra-regional e perspectivas da integração tripartida entre SADC-EACCOMESA. Com base na pesquisa qualitativa coadjuvada pelas técnicas documental e bibliográfica constatou-se que a construção dos processos de integração regional na SADC e EAC evoluiram de padrões de confrontação para cooperação enquanto a COMESA foi por excelência um espaço priviligiado para cooperação comercial. Ainda assim, as três CERs enfrentam mesmos desafios relacionados com a sobreposição dos Estados membros, proliferação de “esquemas informais” de integração regional, dependência das CERs em relação aos doadoers internacionais, fragmentação de mercados nacional e regional e a prevalência da vontade de Estados membros sobre processos de integração regional. Face a estes desafios, a implementação da integração tripartida gera dúvidas e incertezas.
Accepted: 2020-12-17T04:09:38Z
Keywords: COMESA; Desenvolvimento regional; EAC; Integração regional; SADC; Tripartite integration

Algeria and the African Union - between security and economic integration: a neofunctionalist and regionalist reading - Lamri, Amel (Canterbuy Christ Church University, 2020)
This thesis investigates the process of integration in the African Union (AU), and the reasons behind the slow progress of the AU to achieve the goal of deeper economic integration. In the research I explore the role of an AU member state in the process of African integration: Algeria. The research scrutinises the development of Algerian foreign policy towards the AU and highlights any changes in the Algerian FP attitudes and the reasons behind these changes. Similarly, the research unveils the reality of the decision-making process in this country, and the different agents that influence it. To achieve the main goals of the research, different theoretical choices were elaborated. This resulted in researching European integration theories; Neofunctionalism was, then, selected to study the Algerian development in the making of its foreign policy in general and towards the African Union specifically. Some concepts within the Neofunctionalist thinking were used including the principle of the shift of loyalties, the socialisation process, the spillover system, and the role of interest groups in the process of integration. Moreover, the theory of Regionalism was used to examine the process of integration in the AU discovering new reasons that led to the slow development of economic integration in Africa. Consequently, the research highlights the current obstacles and challenges that have hindered the process of economic integration in the AU, including the poverty of most of the AU member states, the limited financial budget of the Union and the instability of the majority of African countries. Furthermore, the research unveiled the lack of political will towards AU economic integration plans. Hence, this contribution extends beyond the traditional models of explanation, and discusses the situation in AU member states (in this case Algeria) and points to other factors as well such as the weakness of the lobbyist activities and business groups in Algeria specifically and Africa more generally. The thesis, then, focusses on Algeria’s supportive and active status in the AU security sector, highlighting how Algeria has been successful in pushing its own security and antiterrorism agenda to the AU level, thereby demonstrating that integration into the AU is possible, if it is backed by influential member states, and wider coalitions can be built to promote integration and cooperation.
Permalink: https://repository.canterbury.ac.uk/item/8y60y/algeria-and-the-african-union-between-security-and-economic-integration-a-neofunctionalist-and-regionalist-reading
Keywords: Africa Union; Algeria; Intégration régionale